Transcending Future Language Learning via Virtual Reality - Nik Aloesnita, Nik Mohd Alwi; Hafizoah, Kassim; Wan Noor Farah, Wan Shamsuddin; Nur Syafawati, Sabuan; Arulselvi, Uthayakumaran (UMPSA, 2023)
JAPAN, 6 October 2023 - Virtual Reality (VR) has evolved rapidly from two-dimensional (2D) text-based online virtual environments to a more sophisticated three-dimensional (3D) virtual spaces and avatars.